KHULU' DALAM PERSPEKTIF FIKIH KLASIK DAN IMPLEMENTASINYA DALAM HUKUM POSITIF INDONESIA - Siti khodijah; Heri Firmansyah (Albayan Journal of Islam and Muslim Societies, 2025)
Khulūʿ, as a divorce mechanism initiated by the wife through the payment of iwāḍ (compensation) to the husband, is a legal institution deeply rooted in classical Islamic jurisprudence, yet it has undergone significant transformation when adopted into modern legal systems, including that of Indonesia. This study reassesses the concept of khulūʿ across the four Sunni schools of law and compares these doctrinal formulations with its judicial implementation within the Indonesian legal system, particularly through the Kompilasi Hukum Islam (KHI) and the practices of the Religious Courts. Employing a qualitative, library-based research approach combined with doctrinal and comparative legal analysis, this research finds that although the fundamental elements of khulūʿ—such as the requirement of iwāḍ, the absence of the husband’s right to revoke the divorce, the prescribed ʿiddah, and the centrality of mutual consent—are maintained, the Indonesian legal system has formally institutionalized khulūʿ by mandating judicial proceedings, requiring specific grounds for divorce, authorizing judicial intervention in determining iwāḍ when no agreement is reached, and introducing administrative procedures absent from classical fiqh discourse. The study concludes that the Indonesian model of khulūʿ reflects a process of Islamic legal adaptation shaped by the demands of modernity, the administrative needs of the state, and the imperative of protecting women, thereby producing a dialectical relationship between fiqh orthodoxy and contemporary family law regulation.